AI dan Moralitas: Refleksi Etis dalam Filsafat Ilmu Pengetahuan - Rina Rohayati; Yusuf Tri Herlambang (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The development of Artificial Intelligence (AI) technology in the Society 5.0 era has a significant impact on various aspects of human life, particularly related to algorithmic bias, privacy, autonomy, and social justice. This study aims to analyze the moral implications of AI through a philosophy of science approach. The research method employs a descriptive qualitative approach with a literature review focusing on the analysis of literature related to ethics in AI development. The findings indicate that ensuring AI functions ethically in the Society 5.0 era requires a comprehensive and humanistic ethical framework. Responsible and sustainable AI development requires an emphasis on fundamental ethical principles such as fairness, transparency, accountability, and responsibility. Ethical theories such as utilitarianism, deontology, and virtue ethics provide guidance to ensure that AI is used fairly, inclusively, and beneficially for all of society. This study also demonstrates that the implementation of AI without ethical considerations and adequate regulation can lead to negative impacts such as exacerbating social inequality, compromising individual privacy, and threatening personal freedom.